Pemanfaatan Daun Nanas Sebagai Bahan Alternatif Dalam Pembuatan Komposit Fiberglass Reinforced Plastic - Marina Marina; Idral Amri; Nirwana Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Composites became one of the alternative materials being developed and widely used in the industrial world. Composites that use natural fibers are chosen because in addition to cheap also environmental friendly. One of the natural fibers that exist around us and has a pretty good potential is pineapple leaf fiber. The purpose of this reasearch is to produce fiberglass reinforced plastic composite using pineapple leaf fiber as an alternative filler, to determine the effect of addition and particle size of pineapple leaf fiber to composite mechanical properties for water treatment plant unit. The composites in this study used pineapple leaf fiber, polyesther resin, methyl ethyl ketone peroxide (MEKPO) catalyst and lubricant. The composite is made through 3 phases of pineapple fiber processing is separation of leaf fiber, fiber drying, and fiber processing into powder and then proceed with the composite making process. Variations were done on pineapple fiber, which as variation of 10%, 20% and 30% fiber addition and fiber particle size variation 60 mesh, 80 mesh and 100 mesh. The results showed that the highest mechanical properties obtained composites with 30% fiber and 100 mesh particle size include: tensile strength 64,672 MPa, flexural strength 430,9 MPa, and modulus of elasticity 5880,7 MPa. The resulting composite meets the standard specification of fiberglass reinforced plastic for water treatment unit based on SNI 7504: 2011.Keywords: composites, fiber, pineapple leaves, polyesther